PERANCANGAN CHASIS KENDARAAN LISTRIK UNIVERSITAS MATARAM - Triadi, A.A. Alit; Rachmanto, Tri; Mara, I Made; Yudhyadi, I G. N. K.; Kaliwantoro, Nur (Energy, Materials and Product Design, 2023)
Chassis is the main component of the vehicle that functions to support the engine, body, suspension system, electrical system and driver. Chassis is one part of the vehicle that has an important role so careful planning is needed in its manufacture. Chassis must be strong and sturdy to support the load of the driver, electric motor and accessories. In addition, the chassis must also be light so as not to overload the work of the electric motor and be able to go through various road conditions. The vehicle body is its function to shape the vehicle and also protect the people inside. In this design, steel and aluminum materials are used, then simulated using the Autodesk Inventor software. The goal is to determine the Von Mosses stress value on the chassis design. AISI 1018 steel material with a load of 700 kg, 800 kg, and with a load of 900 kg obtained a value of 5.56. The safety factor obtained is still safe because it is above the safety factor for industrial construction design, namely 4. Aluminum 6061 material with a load of 700 kg, 800 kg and with a load of 900 kg obtained a value of 7.46. The safety factor obtained is still safe because it is above the safety factor for industrial construction design, namely 4.